2018
DOI: 10.15407/mfint.40.10.1375
|View full text |Cite
|
Sign up to set email alerts
|

On the Advanced Mechanical Properties of Fe–Cu and Y–Cu Nanocomposites Obtained by Mechanical Alloying

Abstract: In this study, the Fe-Cu and Y-Cu nanocomposites are synthesized by mechanical alloying of the elemental powder mixture of the iron, copper and crushed yttrium particles in a high-energy planetary ball mill inside the argon atmosphere. Phase transformations in obtained composite materials are studied by X-ray powder-diffraction methods. The metastable supersaturated α-(Fe, Cu) solid solution is formed in the Fe-Cu nanocomposites during milling process, while the phase transformation during milling of the equia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Multiwalled CNTs used in this experiment were synthesized by the catalytic chemical vapour deposition method (CVD) at TM Spetsmash Ltd. (Kyiv, Ukraine) [5]. Parameters of CNTs are as follows: the average diameter is (10-20) nm, the specific surface area (determined by argon desorption method) is (200-400) m 2 /g and their poured bulk density varies from 20 to 40 g/dm 3 . Both charges were thoroughly mixed and placed into two stainless vials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiwalled CNTs used in this experiment were synthesized by the catalytic chemical vapour deposition method (CVD) at TM Spetsmash Ltd. (Kyiv, Ukraine) [5]. Parameters of CNTs are as follows: the average diameter is (10-20) nm, the specific surface area (determined by argon desorption method) is (200-400) m 2 /g and their poured bulk density varies from 20 to 40 g/dm 3 . Both charges were thoroughly mixed and placed into two stainless vials.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the materials, compacted from the preparing in such way powders, exhibit a nanoscale microstructure and are characterized by an increased microhardness value (almost twice as high as that of bulk YCu obtained by arc melting) and relatively low value of the Young's modulus. More specifically, for these materials, an average value of the Vickers hardness H V is equal to 5.0 GPa and the Young's modulus E is equal to 120 GPa [2,3].…”
Section: Introductionmentioning
confidence: 99%